2015
DOI: 10.5137/1019-5149.jtn.14772-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar stabilization surgery under spinal anaesthesia for patients with degenerative spondylolisthesis, spinal stenosis and lumbar compression fracture

Abstract: AIm:Spinal anesthesia is an appropriate technique for lumbar spine surgeries of two to three hours duration. The aim of this study is to document our experience on spinal anesthesia administered to the patients with degenerative lumbar spine. mAterIAl and methOds: A total of 497 patients underwent spinal stabilization surgery with spinal anesthesia for degenerative lumbar spinal disorders in an 8-year period. Spinal anesthesia was performed at the L3-L4 or L4-L5 level and subarachnoid block was achieved with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…In 2015, concurrent with the present study, Erbas et al 9 reported the results of lumbar fusion surgery with spinal anesthesia in a case series of 497 patients in Turkey. Of these, 119 patients were between the ages of 71 and 84 years.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In 2015, concurrent with the present study, Erbas et al 9 reported the results of lumbar fusion surgery with spinal anesthesia in a case series of 497 patients in Turkey. Of these, 119 patients were between the ages of 71 and 84 years.…”
Section: Discussionsupporting
confidence: 68%
“…In the 3 previously published studies reporting the use of spinal anesthesia for lumbar fusion, the number of levels fused was unclear. [7][8][9] The literature has suggested that spinal anesthesia may offer intraoperative benefits compared with general anesthesia for 1-to 3-level lumbar decompressions. These benefits included decreased blood loss, 1,2 lower mean heart rate, 2,3,6 lower mean arterial pressure (MAP), 2,3,6 and decreased variability in both mean heart rate and mean MAP, 1,4 as well as postoperative benefits such as decreased dependence on narcotics, 1,2 and lower rates of both urinary retention 3,6 and nausea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, few studies report on the application of spinal anesthesia for patients older than 70 years undergoing spine surgery and for procedures lasting more than 2 hours. [1][2][3][4] The authors report the case of an elderly patient with severe spine degeneration who elected for surgery with spinal anesthesia. To the authors' knowledge, this is the most complex lumbar spine fusion performed under spinal anesthesia for a geriatric patient.…”
mentioning
confidence: 99%